Neonatal Thrombocytopenia after Perinatal Asphyxia Treated with Hypothermia: A Retrospective Case Control Study - N. Boutaybi; F. Razenberg; V. E. H. J. Smits-Wintjens; E. W. van Zwet; M. Rijken; S. J. Steggerda; E. Lopriore (International Journal of Pediatrics)
Our objective was to estimate the effect of therapeutic hypothermia on platelet count in neonates after perinatal asphyxia. We performed a retrospective case control study of all (near-) term neonates with perinatal asphyxia admitted between 2004 and 2012 to our neonatal intensive care unit. All neonates treated with therapeutic hypothermia were included in this study (hypothermia group) and compared with a historic control group of neonates with perinatal asphyxia treated before introduction of therapeutic hypothermia (2008). Primary outcome was thrombocytopenia during the first week after birth. Thrombocytopenia was found significantly more often in the hypothermia group than in the control group, 80% (43/54) versus 59% (27/46) (P=.02). The lowest mean platelet count in the hypothermia group and control group was 97×109/L and 125×109/L (P=.06), respectively, and was reached at a mean age of 4.1 days in the hypothermia group and 2.9 days in the control group (P<.001). The incidence of moderate/severe cerebral hemorrhage was 6% (3/47) in the hypothermia group versus 9% (3/35) in the control group (P=.64). In conclusion, neonates with perinatal asphyxia treated with therapeutic hypothermia are at increased risk of thrombocytopenia, without increased risk of cerebral hemorrhage.